Nursing experience of retraining patients with peritoneal dialysis-related peritonitis in a single center (单中心腹膜透析相关性腹膜炎患者再培训的护理体会) - RAN Lei (冉蕾); CHEN Ye (陈叶); LIU Maodong (刘茂东) (中西医结合护理)
Objective To investigated when and how to retraining in peritoneal dialysis(PD) patients and its role in decreasing the incidence of peritonitis according to analysis of the characteristics of peritonitis in the PD center. Methods In a retrospective study, 2 years of data from 2019 before continuous quality improvement(CQI) and 2020 after CQI in our PD center were analyzed. According to analyzing the characteristics of peritonitis before CQI, when and how to retrain PD patients were put forward. The incidence and the characteristics of peritonitis were calculated and analyzed before and after CQI. Results There were 27 episodes of peritonitis in 22 out of total 99 PD patients in 2019. Totally 17 cases with peritonitis occurred for the first time and 11 of them (64. 71%) occurred in their first 6 months after PD initiate. Culture-positive was in 12 episodes (among them, 7 episodes of Coagulase-negative Staphylococcus or Staphylococcus Aureus). The whole year peritonitis rate was 1 episode every 35. 2 months in 2019 before CQI. The first retraining was taken in the third month after PD initiate and redirecting their behavior was made. There were 11 episodes of peritonitis in 10 patients out of 101 patients after CQI in 2020. There were 9 episodes of peritonitis occurred for the first time and 2 of them (22. 22%) occurred in their first 6 months after PD initiate. The rate of culture-positive peritonitis was increased to 63. 64%. In the 7 culture-positive episodes, 3 were Staphylococcus Aureus and 4 were Escherichia coli. The whole year peritonitis rate decreased to 1 episode every 108. 5 months in 2020 after CQI. Conclusion First retraining in the third month after PD initiate and redirecting their behavior to reduce the risk of peritonitis was an effective program in PD center. (目的 分析医院腹膜透析中心腹膜透析相关性腹膜炎发生原因、特点, 探讨再培训的时机、内容及实施效果。方法 选择河北医科大学第三医院腹膜透析中心因终末期肾脏病而行腹膜透析治疗并能规律随访的患者。分析2019年本中心腹膜炎发生率及特点, 根据持续质量改进的原则, 提出再培训的时机、内容、护理流程, 并观察实施效果, 与2020年腹膜透析患者腹膜炎发生率及特点进行比较。结果 2019年99例腹膜透析患者中22例患者发生27例次腹膜炎。全年腹膜炎发生率为1/35. 2个病人月。其中有17例患者首次发生, 11(64. 71%)例发生于腹膜透析置管后的6个月内。12例次培养阳性, 其中凝固酶阴性葡萄球菌及金黄色葡萄球菌感染7例次。将第一次再培训时机设为开始腹膜透析后的第3个月, 主要内容为规范操作。实施再培训后, 2020年本中心101例腹膜透析患者共10例患者发生11例次腹膜炎, 全年腹膜炎发生率为1/108. 5个病人月, 9例首次发生腹膜炎的患者中2(22. 22%)例发生于置管术后6个月内。7(63. 64%)例次培养阳性, 其中金黄色葡萄球菌感染3例次, 大肠杆菌4例次。结论 开展再培训计划, 可使医院腹膜透析中心的腹膜透析相关性腹膜炎的发生率明显减少。)